Spatial patterns and factors influencing population distribution in Zamboanga City 1990-2010 - Sapalleda, Jillian Glaze A. (School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
The increase of Zamboanga City's population size and density time is inevitable. Similarly, increase in population sizes and densities at the barangay level are inevitable. Population sizes and densities of barangays, however, vary: there are those that are larger or that are growing faster compared to others; and there are those with population densities exceeding 50,000 and those still below 500 in 2010. Can population size and density increases be directed of guided location-wise The main objectives of the study are to characterize the spatial patterns of population distribution in Zamboanga City, more specifically the patterns across barangays, and then to examine the factors that may have influenced the pattern in the location of the city's population. The city has unique geographic configuration: the city center barangays are located at a tip of the peninsula and the outer barangays are located along the coastal areas on each of the East and West side of the peninsula. This study examined how population is distributed and how population increase had been accommodated spatially in such a setting. The barangay is used as the unit of analysis in the study; and, thus, land area, population size and population density were quantified by barangay and then analysed across the city's 98 barangays.The findings of the study saw unequal sizes of land area and population across Zamboanga City's barangays. The analysis of the concentration of population showed 80% of the city's population occupying only 20% of its land area. The degree of concentration changed very little at the city level form 1990 to 2010,but population concentration had varied across different areas of the city. Conclusions about densities of barangays include : differences in barangay level population densities reflected the observed inequality in population distribution; barangays in or near the city center have the highest population densities, while inland and high- elevation barangays on the East and West coasts have the least population density; and population density increase was widespread and had occurred in all barangays. Correlation analysis indicated the factors influencing population density and indicated, in turn, characteristics of residential locations preferred by residents. These preferred locations includes the following : being located in or near the CBD, in the West coast, in low elevation (or flat land) and in urban barangays. results from the barangay case studies showed preferred residential locations as those with employment opportunities (higher population density in barangays with industries), with available housing and with good road connections to the CBD. Other factors that brought high level or high increase in barangay population density may actually not be a result of private household preference but rather are due to decisions of private subdivision developers and due to actions of government such as resettlement projects and locating of military bases. One implication of the finding that there was widespread population density increase across the city's barangays is that this could later on lead to a number of environmental and other developmental issues, e.g. exceeding the carrying capacity of coastal and island barangays, and causing damage to environmentally critical areas in high-elevation barangays. But findings of their study also indicate that people respond to specific factors in choosing where to settle and, in fact, government can potentially influence (and direct) locations where population may reside. To address the environmental and development issues just mentioned, the general idea is for government to provide attractive alternative locations that would draw people away from hazardous areas and that would slow down movement into congested urban centers through instruments such as the zoning ordinance.